L Chromosome Behaviour and Chromosomal Imprinting in Sciara Coprophila - Singh, Prim B.; Belyakin, Stepan (My University, 2018)
The retention of supernumerary chromosomes in the germ-line of Sciara coprophila is part of a highly-intricate pattern of chromosome behaviours that have fascinated cytogeneticists for over 80 years. Germ-line limited (termed L or “limited”) chromosomes are cytologically heterochromatic and late-replicating, with more recent studies confirming they possess epigenetic hallmarks characteristic of constitutive heterochromatin. Little is known about their genetic constitution although they have been found to undergo cycles of condensation and de-condensation at different stages of development. Unlike most supernumeraries, the L chromosomes in S. coprophila are thought to be indispensable, although in two closely related species Sciara ocellaris and Sciara reynoldsi the L chromosomes, have been lost during evolution. Here, we review what we know about L chromosomes in Sciara coprophila. We end by discussing how study of the L chromosome condensation cycle has provided insight into the site and timing of both the erasure of parental “imprints” and also the placement of a putative “imprint” that might be carried by the sperm into the egg.
Keywords: supernumerary chromosomes; heterochromatin; parent-of-origin effects; paternal X chromosome; maternal X chromosome; controlling element